2019
DOI: 10.3390/cancers12010041
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α6β4 in Colorectal Cancer: Expression, Regulation, Functional Alterations and Use as a Biomarker

Abstract: Integrin α6β4 is one of the main laminin receptors and is primarily expressed by epithelial cells as an active component of hemidesmosomes. In this article, after a brief summary about integrins in the gut epithelium in general, I review the knowledge and clinical potential of this receptor in human colorectal cancer (CRC) cells. Most CRC cells overexpress both α6 and β4 subunits, in situ in primary tumours as well as in established CRC cell lines. The mechanisms that lead to overexpression have not yet been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 73 publications
4
33
0
Order By: Relevance
“…This multi-protein complex is anchored by integrin α6β4, and both α6 and β4 showed significant and substantial decreases in HCT116-GSK3β-KO cells. Integrins α6 and β4 were the only integrins identified in our study as significantly differentially expressed, consistent with the observation that in epithelial cells β4 only dimerizes with α6 subunit in an exclusive association (23). We investigated the strength of cell-cell adhesion and found that HCT116-GSK3β-KO were significantly less adherent than HCT116-GSK3β-WT cell films consistent with the proteomic data indicating major hemidesmosome disruption.…”
Section: Dysregulated Carbon Metabolism In Gsk3β Knockout Cellssupporting
confidence: 89%
“…This multi-protein complex is anchored by integrin α6β4, and both α6 and β4 showed significant and substantial decreases in HCT116-GSK3β-KO cells. Integrins α6 and β4 were the only integrins identified in our study as significantly differentially expressed, consistent with the observation that in epithelial cells β4 only dimerizes with α6 subunit in an exclusive association (23). We investigated the strength of cell-cell adhesion and found that HCT116-GSK3β-KO were significantly less adherent than HCT116-GSK3β-WT cell films consistent with the proteomic data indicating major hemidesmosome disruption.…”
Section: Dysregulated Carbon Metabolism In Gsk3β Knockout Cellssupporting
confidence: 89%
“…Prevention of αV, α6, and β1 up-regulation by SFN or the SFN-everolimus combination could, therefore, immobilize tumor cells to impede cancer progression. Down-regulation of β4 by SFN and, even more so by SFN combined with everolimus, indicates that β4, which mediates pro-migratory and pro-proliferative properties [ 31 , 32 ], could serve as a potential therapeutic target [ 33 ]. Since the combination with everolimus was superior to SFN alone, SFN may re-sensitize tumor cells to everolimus, similar to it re-sensitizing tumor cells to tamoxifen or lapatinib [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that BNIP1 could restrain cervical cancer cell proliferation, migration and invasion by inhibit mTOR signaling pathway, although it seemed to be a risky factor in UM patients [ 26 ]. Integrin subunit α 6 (ITGA6), a member of the integrin α chain family of proteins, is an efficient early-detection biomarker and prognostic factor for colorectal cancer patients [ 27 ]. FKBP1A belongs to immunophilin protein family and mediate the immunosuppressive and antitumor effects of rapamycin [ 28 ].…”
Section: Discussionmentioning
confidence: 99%